The impact of chronic diseases and lifestyle on sarcopenia risk in older adults: a population-based longitudinal study - Wei, Wu-xiao; Mao, Zhen-fang; Chen, Meng-li; Meng, Lian (Frontiers in Medicine, 2025)
BackgroundSarcopenia, characterized by the gradual decline of muscle mass and strength, seriously affects the health and mobility of older adults. The purpose of this study is to investigate the risk factors for sarcopenia, particularly the relationship between chronic diseases and lifestyle factors in individuals aged 60 and over.MethodsThis study used data from the Longitudinal Study on Health and Retirement in China (CHARLS) collected in 2011 and 2015. All eligible participants were classified according to the standards established by the Asian Sarcopenia Working Group in 2019. The evaluation of sarcopenia was based on a comprehensive score across five dimensions: strength, assistance in walking, rise from a chair, climb stairs, and falls. A multivariate logistic regression model was employed to explore the risk factors for sarcopenia.ResultsThe risk of sarcopenia is significantly influenced by multiple factors. Key findings include the association between past drinking and an increased risk of sarcopenia (HR = 2.198, 95% CI: 1.072–4.560, p < 0.05), indicating that individuals with a history of drinking have more than twice the risk of sarcopenia compared to non-drinkers. Chronic diseases such as stroke were also associated with a significantly elevated risk (HR = 3.137, 95% CI: 1.128–8.721, p < 0.05). Conversely, participation in social activities significantly reduced the risk of sarcopenia (HR = 0.482, 95% CI: 0.265–0.876, p < 0.05). A three-piece spline regression model revealed a nonlinear relationship between physical activity and the risk of sarcopenia, characterized by an initial decline in risk followed by an increase as physical activity levels rose. Moderate-intensity physical activity reduced the risk of sarcopenia by approximately 35% (HR ≈ 0.65). However, high-intensity physical activity led to a rebound in risk, increasing the likelihood of sarcopenia relative to moderate activity. Similarly, adequate sleep duration was associated with a reduced risk of sarcopenia, whereas excessive sleep counteracted this benefit.ConclusionThe findings underscore the critical role of lifestyle modifications and balanced physical activity in mitigating the risk of sarcopenia among older adults. Implementing targeted interventions for high-risk groups is essential to reduce the incidence of sarcopenia.